Pengaruh Beban Pajak Tangguhan, Green Intellectual Capital, dan Kebijakan Utang terhadap Kinerja Perusahaan - Irsyad Asy’ari; Dian Widiyati (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
This research aims to reveal the influence of deferred tax expense, green intellectual capital, and debt policy on company performance. This type of research uses associative quantitative research methods. The population in this research are Basic Materials sector companies listed on the Indonesia Stock Exchange in 2021-2023. The sampling technique in this research is based on purposive sampling technique. It is known that as many as 106 companies are listed on the Indonesian Stock Exchange in the Basic Materials sector. With the sample selection criteria, a sample of 24 companies was obtained, so the total number of data observations was 72. This research uses statistical tools, namely eviews software version 12. The analysis technique used is data regression. panel. The research results show that deferred tax expense, green intellectual capital, and debt policy simultaneously have a significant effect on company performance. Meanwhile, partially it shows that the deferred tax expense has no effect on company performance. green intellectual capital influences company performance. Debt policy influences company performance.